Stock Returns on Option Expiration Dates - CHIANG, Chin-Han (Institutional Knowledge at Singapore Management University, 2010)
This paper documents striking evidence that stocks with a sufficiently large amount of deeply in-the-money call options earn signficantly lower returns on option expiration dates, with a drop in average daily returns of up to 0.8 percentage point. This price movement of stocks is followed by a reversal. On option expiration dates, option holders who exercise deeply in-the-money call options have an increasing demand for immediacy to sell the acquired stocks in the stock market. I offer an explanation of why this is not offset by option writers’ purchases, based on the premise that most written calls are covered either at inception or prior to maturity. When exercised open interest is sufficiently large compared to the daily trading volume of the underlying stocks, the resulting selling pressure in the stock market leads to a fall in expiration-date returns of the underlying stocks.